Chronic Appendicitis: Diagnostic Dilemma in Female Patient for Recurrent Lower Abdominal Pain - Nahar, Khairun; Hossain, SM Amjad; Khatun, Ashia (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Many female patients presented to gynecologist with chronic lower abdominal pain, suspecting chronic PID or UTI, but found no improvement inspite of repeated treatment. It remains as diagnostic dilemma for gynaecologist. Proper diagnosis ultimately shows that it is a case of chronic appendicitis. The main purpose of this study was to evaluate the clinical feature of chronic appendicitis and its correlation with operative and histological findings & to create alertness of physicians and prevention of later complication. Methods: This cross-sectional study was carried out in female patients in private practice from January 2014 to December 2017.All patientswho complained frequent attacks of pain in their right lower abdomen were included in our study. The patient’s history, clinical and lab findings were closely evaluated. All the patients underwent appendectomy and all their appendices were histopathologically examined. Chronic appendicitis was ruled in with a positive pathology report confirming chronic inflammation. All the patients referred for their follow-up visits in a period of one year. Results: A total100 female patients were studied.66% patient were in age group 26 to35 years.87% patients were multiparous. Duration of pain varied from 2weeks to 2.5 years. Histopathology report confirmed chronic appendicitis in 96% cases. From them 94% cases expressed complete relief of pain following removal in the follow-up visit. Conclusion: Chronic appendicitis seems to be a cause of recurrent lower abdominal pain. The disease is easily cured by appendectomy. J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 59-61